The Statistical Complement of Pure Economics - Moore, Henry L. (Quarterly Journal of Economics, 1908)
Representative constructive workers in pure economics have conceived of an inductive statistical complement without whose development the a priori instrument must lack concrete effectiveness, 1.— The most important statistical processes that must be employed in the elaboration of the inductive science are described, 8.—Steps which have already been taken in the attempt to bring together pure economics and the theory of statistics in the treatment of concrete material are illustrated, 23.—From a survey of what has been accomplished it is inferred that fecund scientific ideas as well as abiding practical results are to be gained from the development of the Statistical Complement of Pure Economics, 33.